THE STUDY OF FORMULATION COCONUT MILK AND AGAR IN MAKING OF KERIBANG (Dioscorea alata) ICE CREAM - Yusup Nurahman; Tri Rahayuni; Eva Mayasari (Jurnal Sains Pertanian Equator, 2019)
This research wasaimed to determine thebest characteristicofformulation coconutmilk andagarinmakingofkeribang(Dioscoreaalata)icecream.Theexperimentaldesignedusing RandomizedBlockDesign(RBD)wichisconsisttwofactorofcoconutmilk(200g,250g,300g) andagar (3g,4g,5g),eachtreatmentwas replicated threetimes.Themeasuredparameters werephisycal,chemical, and sensorycharacteristics.ThedataofPhisycalandchemicalwere analyzed statisticallyusing ANOVA(α=5%) andHSDTest(α=5%)and sensorytestwas analyzedbyKruskalWallis.Thebesttreatmentwasdeterminedbyusing methodof effectivenessindex.Theresultshowedkeribang ice creamwithadditionofcoconutmilk250g andAgar4gwasthebesttreatmentwith chemical characteristicswerefatcontent27.84%, proteincontent1.70%,totaldissolved solids20.80°brix,Physicalcharacteristicswereoverrun 20.55%,high-speedmelting25.19minutes,andsensoryvalues resultedof taste5.40(like), texture5.23 (like), color5.53 (likeverymuch), aroma 4.70 (like).This reseach was aimed to determine the best characteristic of formulation coconut milk and agar in making of keribang (Dioscorea alata) ice cream. The experimental designed usingRandomized Block Design (RBD) wich is consist two factor of coconut milk (200g, 250g, 300g)and agar (3g, 4g, 5g), each treatment was replicated three times. The measured parameterswere phisycal, chemical, and sensory characteristics. The data of Phisycal and chemical wereanalyzed statistically using ANOVA (α=5%) and HSD Test (α=5%) and sensory test wasanalyzed by Kruskal Wallis. The best treatment was determined by using method ofeffectiveness index.  The result showed keribang ice cream with addition of coconut milk 250gand Agar 4g was the best treatment with chemical characteristics were fat content 27.84%,protein content 1.70%, total dissolved solids 20.80°brix, Physical characteristics were overrun 20.55%, high-speed melting 25.19 minutes, and sensory values resulted of taste 5.40 (like),texture 5.23 (like), color 5.53 (like very much), aroma 4.70 (like).